2018
DOI: 10.1002/jcph.1103
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Doses of Rifabutin Reduce Exposure of Doravirine in Healthy Subjects

Abstract: Doravirine is a nonnucleoside reverse transcriptase inhibitor in clinical development for the treatment of human immunodeficiency virus-1 infection in combination with other antiretroviral therapies. The cytochrome P450 (CYP)3A-dependent metabolism of doravirine makes it susceptible to interactions with modulators of this pathway, including the antituberculosis treatment rifampin. Rifabutin, an alternative antibiotic used to treat tuberculosis, may have a lower-magnitude effect on CYP3A. The aim of this trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 22 publications
4
42
0
Order By: Relevance
“…14,15 To date, preclinical and clinical data suggest that doravirine has minimal drug-drug interactions (DDIs) [18][19][20][21][22] as doravirine is not expected to either induce or inhibit any of the major CYP enzymes or transporters. 20,22,[26][27][28] Consistent with this finding, the majority of an absorbed oral dose of [ 14 C]-labeled doravirine in healthy subjects was recovered as oxidative metabolites. 24 Low clearance (3.73 L/hr) and a moderate volume of distribution (60.5 L) were observed following intravenous administration of doravirine.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…14,15 To date, preclinical and clinical data suggest that doravirine has minimal drug-drug interactions (DDIs) [18][19][20][21][22] as doravirine is not expected to either induce or inhibit any of the major CYP enzymes or transporters. 20,22,[26][27][28] Consistent with this finding, the majority of an absorbed oral dose of [ 14 C]-labeled doravirine in healthy subjects was recovered as oxidative metabolites. 24 Low clearance (3.73 L/hr) and a moderate volume of distribution (60.5 L) were observed following intravenous administration of doravirine.…”
supporting
confidence: 63%
“…25 In vitro studies and clinical drug interaction studies indicated that CYP3A-mediated metabolism is a major contributor to the elimination of doravirine. 20,22,[26][27][28] Consistent with this finding, the majority of an absorbed oral dose of [ 14 C]-labeled doravirine in healthy subjects was recovered as oxidative metabolites. The oxidative metabolite M9 was the major metabolite of doravirine observed both in vitro in preparations from human liver and in vivo in human excreta and plasma.…”
supporting
confidence: 63%
“…Doravirine displays a 95% effective concentration of 20, 43, 27, and 55 nM against the WT, K103N, Y181C, and K103N/Y181C mutant viruses, respectively, in the presence of 50% human serum. 7 Doravirine is not highly bound to plasma protein (ß75%), and in vitro studies 8 as well as clinical drug-drug interaction trials conducted with modulators of CYP3A metabolism [9][10][11] suggest that CYP3A plays a major role in the metabolism of doravirine; less than 10% of doravirine is eliminated via renal excretion. 12 In a double-blind study involving healthy subjects, doravirine was demonstrated to be generally well tolerated over the dose range of 6-1200 mg. 4 The pharmacokinetic (PK) profile of these doses was investigated in the same study, and doravirine was demonstrated to achieve maximum plasma concentration (C max ) after 1-5 hours with an apparent terminal half-life (t 1/2 ) of 12-21 hours.…”
mentioning
confidence: 99%
“…17 In vitro studies and clinical drug interaction studies indicated that cytochrome P450 (CYP)3A-mediated metabolism plays a major role in the elimination of doravirine. [17][18][19][20][21] Consistent with this, following oral administration of [ 14 C]-labeled doravirine to healthy subjects, the majority of the absorbed dose was recovered as oxidative metabolites, with minor amounts of conjugation products observed in excreta or in plasma. The major metabolite of doravirine observed in vitro in preparations from human liver and in excreta and plasma from humans was an oxidative metabolite.…”
mentioning
confidence: 77%
“…20 Similarly, multiple dosing of the CYP3Ainducer rifabutin resulted in clinically meaningful reductions in doravirine exposure, requiring twice-daily administration of doravirine to compensate. 21 The clinical PK of doravirine and potential DDIs after the coadministration of commonly prescribed drugs has been previously reviewed. 27 As metformin is a commonly prescribed medication in individuals infected with HIV-1 who have type 2 diabetes mellitus, doravirine and metformin may be coadministered to treat both conditions.…”
mentioning
confidence: 99%